Analisis Finansial Usaha Penangkapan Ikan dengan Alat Tangkap Soma Pajeko di Desa Tumbak Kecamatan Pusomaen Kabupaten Minahasa Tenggara - Pananginan, Elshaday C.; Durand, Swenekhe S.; Manoppo, Victoria E.N.; Andaki, Jardie A.; Pangemanan, Jeannette F.; Aling, Djuwita R.R. (Universitas Sam Ratulangi, 2024)
Abstract The purpose of this study is to describe the general conditions and financially analyze the fishing business using Soma Pajeko fishing gear in Tumbak Village, Pusomaen District, Southeast Minahasa Regency. The basic method used in this study is a survey. The data collected consists of primary data and secondary data. Data collection was carried out through observation, interviews, questionnaires and documentation, both photo documentation and taking written documents from related agencies. The data obtained were analyzed using quantitative and qualitative descriptive analysis. Financial analysis aims to determine estimates in terms of funding and cash flow, so that it can be known whether or not the business being run is feasible. The soma pajeko fishing gear business in Tumbak Village that was analyzed was Operating profit of IDR 260,160,000, Net profit of IDR 187,773,000, Profit rate of 121.18%, Benefit cost ratio of 2.21 or> 1, BEP Sales of IDR 95,246,710, BEP unit 5,952 kg. Keywords: financial analysis; soma pajeko; Tumbak Village Abstrak Tujuan penelitian ialah mendeskripsikan keadaan umum dan menganalisis secara finansial usaha penangkapan ikan dengan menggunakan alat tangkap Soma Pajeko di Desa Tumbak Kecamatan Pusomaen Kabupaten Minahasa Tenggara. Metode dasar yang digunakan dalam penelitian ini yaitu survei. Data yang dikumpulkan terdiri dari data primer dan data sekunder. Pengumpulan data dilakukan melalui observasi, wawancara, kuisioner dan dokumentasi baik itu dokumentasi foto maupun pengambilan dokumen tertulis pada instansi terkait. Data yang diperoleh di analisis dengan analisis deskriptif kuantitatif dan deskriptif kualitatif. Analisis finansial bertujuan untuk mengetahui perkiraan dalam hal pendanaan dan aliran kas, sehingga dapat diketahui layak atau tidaknya bisnis yang dijalankan. Usaha alat tangkap soma pajeko yang ada di Desa Tumbak yang dianalisis adalah Operating profit Rp260.160.000, Net profit Rp187.773.000, Profit rate 121,18%, Benefit cost ratio 2,21 atau >1, BEP Penjualan Rp95.246.710 , BEP satuan 5.952 kg. Kata kunci : analisis finansial; soma pajeko; Desa Tumbak